The effect of ascorbic acid and soybean protein hydrolysate to iron binding capacity - Sri Peni Wijayanti; Erma Maryana; Ida Susanti; Noer Laily (Current Research on Bioscences and Biotechnology, 2020)
The study aimed to investigate the effect of ascorbic acid and soybean protein hydrolysate to iron-binding capacity. BPPT (Agency for the Assessment and Application of Technology) developed soybean hydrolysate, which was obtained by thermal and enzymatic hydrolysis. Ascorbic acid was added in sample preparation with composition 0, 50, 75 and 100%. Soybean protein hydrolysate (SPH) was prepared by gel filtration chromatography using Sephadex G-25 to separate peptide based on molecular weight. Characterization of SPH and SPH fractions was also conducted, such as protein concentration, molecular weight, iron-binding capacity, and amino acid concentration. Iron binding capacity was determined by the colorimetric method using an ortho-phenanthroline reagent. The result showed that soybean protein hydrolysate increases iron-binding capacity 25-37 times than ascorbic acid. Arginine, aspartic acid, glutamic acid, threonine, lysine, and serine were found as amino acids responsible for iron-binding capacity in the SPH.